Patriotism and Propaganda in First World War Britain : the National War Aims Committee and Civilian Morale - Monger, David (Cambridge University Press, 2013)
This book is the first comprehensive investigation of the British National War Aims Committee during the First World War, providing detailed discussion of the establishment, activities and reception of the British domestic propaganda organisation, together with a careful and extensive analysis of the patriotic content of its propaganda.